Improved camouflage through ontogenetic colour change confers reduced detection risk in shore crabs - Nokelainen, Ossi; Maynes, Ruth; Mynott, Sara; Price, Natasha; Stevens, Martin (Functional ecology, 2019)
Animals from many taxa, from snakes and crabs to caterpillars and lobsters, change appearance with age, but the reasons why this occurs are rarely tested. We show the importance that ontogenetic changes in coloration have on the camouflage of the green shore crabs (Carcinus maenas), known for their remarkable phenotypic variation and plasticity in colour and pattern. In controlled conditions, we reared juvenile crabs of two shades, pale or dark, on two background types simulating different habitats for 10 weeks. In contrast to expectations for reversible colour change, crabs did not tune their background match to specific microhabitats, but instead, and regardless of treatment, all developed a uniform dark green phenotype. This parallels changes in shore crab appearance with age observed in the field. Next, we undertook a citizen science experiment at the Natural History Museum London, where human subjects (“predators”) searched for crabs representing natural colour variation from different habitats, simulating predator vision. In concert, crabs were not hardest to find against their original habitat, but instead, the dark green phenotype was hardest to detect against all backgrounds. The evolution of camouflage can be better understood by acknowledging that the optimal phenotype to hide from predators may change over the life history of many animals, including the utilization of a generalist camouflage strategy. A plain language summary is available for this article. Plain Language Summary